1997
DOI: 10.1002/(sici)1097-4652(199712)173:3<351::aid-jcp7>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Expression cloning of a mammalian amino acid transporter or modifier by complementation of a yeast transport mutant

Abstract: A cDNA clone named L21 was isolated from L6 rat muscle cells by complementation of a yeast proline transport mutant. L21 cDNA has 2,268 bp and codes for a peptide of 228 amino acids with four potential transmembrane domains. The amino acid sequence of L21 shows no homology to any known proteins. Expression of L21 cDNA enables the mutant yeast to grow in proline as the sole nitrogen source and to transport proline, alpha-aminoisobutyric acid (AIB) and leucine. The Km for proline is about 1.0 mM. The substrate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…However, the characteristics and splicing mechanisms of yeast introns are different from those of filamentous fungi (Gurr et al ., 1987). In yeast, no requirement for the presence of introns has been observed when genes from plants or vertebrates were expressed (Hiraiwa et al ., 1997; Lin et al ., 1997). In contrast to introns in genes from animals, S. cerevisiae and plants, introns of filamentous fungi are characteristically short (on average less than 100 bp).…”
Section: Discussionmentioning
confidence: 99%
“…However, the characteristics and splicing mechanisms of yeast introns are different from those of filamentous fungi (Gurr et al ., 1987). In yeast, no requirement for the presence of introns has been observed when genes from plants or vertebrates were expressed (Hiraiwa et al ., 1997; Lin et al ., 1997). In contrast to introns in genes from animals, S. cerevisiae and plants, introns of filamentous fungi are characteristically short (on average less than 100 bp).…”
Section: Discussionmentioning
confidence: 99%
“…Xu and Gong (2003) showed that introns are required for AFP gene (a gene encoding antifungal protein in A. giganteus) expression in T. atroviride transformants, as demonstrated by the level of mRNA and confirmed by analysis of AFP synthesis. In contrast, in the ascomycetous yeast S. cerevisiae only 2 to 5% of the genes contain introns and no obligation for introns has been observed for vertebrate and plant genes expression (Hiraiwa et al, 1997;Lin et al, 1997). However, less is even known about intron-dependent mRNA accumulation in fungi and further researches should be accomplished.…”
Section: The Use Of Native or Artificial Intron-containing Genes In Fmentioning
confidence: 99%